The Efficiency of Aboriginal Entomopathogenic Nematodes from Semi-Arid Zone Against Tenebrionidae Larvae with Comparison to Commercial Bio-Insecticides - Dauren Kaliaskar; Aigerim Shibaeva; Nariman Zhappar; Valentin Shaikhutdinov; Laura Asherbekova; Sayakhat Bekbulatov; Almagul Kalyaskarova (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2022)
Chemical insecticides are intensively used in agriculture which cause negative effects on environmental sustainability by increasing pest tolerance and continuous action on local fauna. In contrast to chemical insecticides, biological insecticides target specific pests, minimizing their impact on the surrounding environment. However, most of the natural insecticides available in the market are expensive for farmers in the Central Asian region. This study is the first evidence of the effectiveness of local entomopathogenic nematodes (EPN) from the arid zone of northern Kazakhstan that can be used as an alternative to export EPN products. The laboratory experiment is conducted with two local and two commercial Steinernema feltiae and Steinernema carpocapsae, which are applied to larvae of Tenebrionidae. The experiment design is randomized with four doses of EPN (100, 200, 300, and 400 IJ/cm2) and a control (without EPN). According to the experiment results, one out of two local EPNs (AF29 at dose 100 IJ/cm2) caused a high mortality rate (67%) among larvae. This finding confirms that local EPNs can compete with commercial EPNs and potentially be used as insecticidal agents.